Outsourcing Legal Aid in the Nordic Welfare States - Halvorsen Rønning, Olaf; Hammerslev, Ole (Springer Nature, 2018)
Socio-legal studies; Law; Criminology; Criminal justice; Action research; Scandinavia; Welfare state; Norway; Demark; Finland; Sweden; Iceland